Local Anaesthetic Properties vs. Neurotoxicity for (+)- and (−)-Carvone: An Ex Vivo Electrophysiological Study - Faliagkas, Leonidas; Vokou, Despoina; Theophilidis, George (Planta Medica Letters, 2015)
The two carvone enantiomers were tested for local anaesthetic activity at concentrations of 10 and 20 mM using a nerve preparation based on the isolated sciatic nerve of the frog and were found to induce similar responses. They eliminated the evoked compound action potential within 6–7 min, while there was an instant 83 to 87 % recovery when they were washed out from the nerve preparation and replaced with normal saline. Both carvones have the same pattern of action as 10 mM lidocaine, the standard local anaesthetic, but they are 3–4 times less active with respect to the time of response. When the nerves were exposed to the carvones for a period of time longer than 6–7 min, for example 1 h, there was no recovery at all of the evoked compound action potential, indicating a neurotoxic action. In contrast, when nerves were exposed under the same conditions to lidocaine and another natural compound with local anaesthetic properties, 2-heptanone, there was an 80–100 % recovery. This unusual neurotoxic effect of (+)- and (−)-carvone can be a disadvantage for their use in clinical practice.
Keywords: (+)-carvone; (−)-carvone; local anaesthetic; neurotoxic; sciatic nerve; electrophysiology